(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article is devoted to the study of the theoretical aspects of national security and technologies of interaction between states and Parliaments. Analysis of political tasks and technologies of interaction between the state and the Jogorku Kenesh of the Kyrgyz Republic, which, through the prism of manipulative, normative, marketing, structural-functional, communicative and comparative approaches, made it possible to present models using the example of manipulation as a multidimensional socio-political phenomenon, as well as an integrated interdisciplinary system of knowledge.